Effect of boron oxide on stability of high-ferrite Portland cement clinker in low-temperature calcination - Xiao Huang; Jinfang Zhang; Kechang Zhang (Scientific Reports)
Abstract This study delves into the challenges posed by the low-temperature calcination of high-ferrite Portland cement (HFPC) clinker and explores the potential of boron oxide (B2O3) as a stabilizing agent. Clinker production is a major contributor to global carbon dioxide emissions, and finding sustainable solutions is paramount. At 1350 °C, the HFPC clinker exhibits severe pulverization due to the metastable nature of the C2S phase formed at low temperature. To address these challenges, various stabilizing agents, including K2O + Na2O, barium carbonate (BaCO3), calcium fluoride (CaF2), and B2O3, were investigated. K2O + Na2O, BaCO3, and B2O3 exhibited promising stabilization effects, although K2O + Na2O negatively impacted the stability, and BaCO3 resulted in significant retardation. Consequently, B2O3 was chosen as the preferred stabilizing agent for the low-temperature calcination of HFPC clinker. However, it was observed that the B2O3 content should not exceed 1% to prevent destabilization of the C3S phase, which affects early-stage strength development. This research contributes to the understanding of HFPC clinker stability under low-temperature conditions and provides a potential avenue for reducing energy consumption and carbon emissions in HFPC clinker production.